Effect of energy density on laser powder bed fusion built single tracks and thin wall structures with 100 µm preplaced powder layer thickness. (May 2020) - Nayak, S.K.; Mishra, S.K.; Paul, C.P.; Jinoop, A.N.; Bindra, K.S.
Highlights: Laser Powder Bed Fusion of single tracks and thin walls at 100 μm layer thickness. Process window identified in terms of energy density for stable single tracks. Parametric investigation on track morphology, track geometry and wall geometry. Analytical and regression models developed for track and wall geometry. Geometrical variation from single track to thin walls investigated. Abstract: Laser Powder Bed Fusion (LPBF) is one of the advanced manufacturing technologies used for fabricating near net shaped components directly from CAD model data by selectively melting pre-placed layer of powder in layer by layer fashion. LPBF process is widely researched with layer thickness up to 60 µm and is now commercially deployed for many metallic materials. However, very limited literature is available in public domain for LPBF with layer thickness >60 µm as the process in this window has many challenges in geometry control and reproducibility due to inherent process instability. However, higher layer thickness with larger beam diameter can bring better productivity and shorter built time with limited compromise on minimum feature size. The present work focuses on a systematic parametric study on single track and thin wall fabrication using LPBF at layer thickness of 100 µm by varying laser power (150–450 W) and scan speed (0.02–0.08 m/s) using SS 316L powder. For the range of parameters under investigation, process window yielding stable tracks (regular and uniform) is obtained for energy density between 87.5 and 140 J/mm 3 . An analytical model for predicting the width of the track and a regression model for the depth of re-melted zone in the substrate subsurface and track area during single track fabrication is developed in terms of energy density. The average difference in predicted and experimental values for width and area of the track are 3.18% and 7.61%, respectively within the process window. Width of thin walls built at the same parameters is measured and the variation between width of thin wall and track is estimated in terms of energy density. The width of thin walls fabricated are observed to be larger than that of single track built at the same combinations of process parameters primarily due to preheating effect. For the range of parameters under investigation, the highest values of width of thin wall and its difference from corresponding width of track is observed at 112.5 J/mm 3 in the process window. The study paves a way in understanding the effect of higher layer thickness on the geometry of LPBF built components.